Sustainable leadership: A literature review and prospects for future research - Liao, Yaohua (Frontiers in Psychology, 2022)
The various social issues that accompany economic development pose new challenges for leaders to integrate economic benefits, social responsibility and environmental protection. In this context, various new leadership styles have emerged. Among them, sustainable leadership reveals the key role of leaders in balancing the triple goals of economy, society and environment, and has become an important part of leadership theory research in recent years. We searched the literature related to sustainable leadership in databases such as Web of Science, EBSCO and CNKI. Based on the existing literature, we systematically review the origins, connotations, analytical perspectives, measurement methods and conceptual comparisons of sustainable leadership. And we also construct an integrated analytical framework of sustainable leadership on the premise of sorting out and summarizing the antecedents and consequences of sustainable leadership. Finally, we provide an outlook on the future research areas of sustainable leadership in order to further promote research of sustainable leadership.